miR-509 inhibits cancer stemness properties in oral carcinomas via directly targeting PlK1 - Ming-Yi Lu; Chih-Yuan Fang; Pei-Ling Hsieh; Yi-Wen Liao; Lo-Lin Tsai; Cheng-Chia Yu (Elsevier, 2022)
Background/purpose: Oral cancer is one of the common cancers worldwide. Emerging evidence has indicated that microRNAs (non-coding RNA molecules of approximately 22 nucleotides in length) are implicated in the regulation of cancer stemness. However, the functional role of microRNA-509 (miR-509) in the characteristics of oral cancer stem cells (CSCs) has not been unraveled. Materials and methods: The expression level of miR-509 in ALDH1+ and sphere oral CSCs was examined by qRT-PCR. The aldehyde dehydrogenase 1 (ALDH1) activity and CD44 expression were assessed using flow cytometry. Self-renewal, transwell migration, and colony formation assays were conducted to measure the CSC phenotypes. Besides, a luciferase reporter assay was used to confirm the direct interaction between miR-509 and its target polo-like kinase 1 (plk1). Results: We showed the expression of miR-509 was downregulated in the CSCs derived from oral cancer cells (SAS), and upregulation of miR-509 diminished the several CSCs features, including ALDH1 activity, self-renewal capacity, CD44 expression, migration, and colony-forming abilities. Moreover, the result from the luciferase reporter assay validated the direct binding of miR-509 to plk1. Conclusion: Our results suggest that the miR-509/plk1 axis may mediate the cancer stemness in oral cancer, and targeting this axis may attenuate the progression of oral cancer.